Potêncial energético para geração de energia elétrica a partir de resíduos sólidos urbanos em Belém do Pará: revisão de literatura - FREITAS, Naldson Silva de (2023)
The disposal of Municipal Solid Waste (MSW) is a task that requires careful management and planning, the biggest challenge being to find a solution that is economically viable and environmentally sustainable. The city of Belém, one of the largest cities in the state of Pará, faces its own problems in terms of the management and final destination of municipal solid waste, and as it is a very populous city, it consequently generates a high level of MSW. However, through the data collected in this study, it was observed that MSW can be reused as a source of energy with the help of evolving mechanisms and appropriate management practices. The aim of this study was to search the literature for methodologies/resources that present Belém do Pará's energy potential for generating electricity from municipal solid waste. In addition, the work methodology was based on a systematic review of the literature over the last 10 years using Google Scholar, the Coordination for the Improvement of Higher Education Personnel (CAPES) and the Brazilian Digital Library of Theses and Dissertations (BDTD) as a research base. Keywords and exclusion and inclusion criteria were determined for the research, resulting in 25 papers for analysis. It can be concluded that using MSW to generate energy offers numerous advantages, such as reducing the volume of waste in landfills, mitigating greenhouse gas emissions, creating job opportunities and providing a renewable energy source to help the country achieve energy balance.